Pendampingan Pastoral bagi Jemaat yang Mengalami Perceraian: Kajian Teologis dan Praktis - Pinata Pinata; Cirma Nalika Datu Linggi; Jafriyani Parammangan (International Forum of Researchers and Lecturers, 2026)
Divorce is an increasing social reality within Christian congregations, including in Indonesia, bringing profound psychological, social, and spiritual impacts while simultaneously presenting serious challenges for the church's pastoral ministry. This article examines the theological foundation and practical approaches in pastoral accompaniment for congregation members experiencing divorce, employing library research methodology within a pastoral theology framework. The study reveals that the church is called to be present not as a judge, but as a healing, supportive, and restoring community. Effective pastoral accompaniment encompasses empathetic pastoral counseling, a compassionate congregational community, intentional attention to affected children, and a long-term restoration commitment rooted in Gospel grace. The church is called to move beyond stigmatization toward genuine acceptance of wounded individuals, reflecting the redemptive love of Christ. This article concludes that the church's response to divorce must balance biblical integrity with deep compassion, affirming both the sanctity of marriage and the dignity of broken individuals. Thus, the church can become a safe space for every congregation member to experience genuine restoration and rediscover hope in Christ.